PERAN EKSTRAKURIKULER UNTUK MENGEMBANGKAN BAKAT DAN MINAT ANAK DI SDN AENGDAKE I - Andika Ufuk Rizkiyanto; Ibnu Sattar Amalih; Mas’odi (Kampus Akademik Publiser, 2025)
This research aims to illustrate the importance of extracurricular activities in developing students' talents and interests at SDN Aengdake I. Extracurricular activities such as sports and scouting are a means to shape character, improve social skills, and support students' holistic development. With a qualitative descriptive approach, this research utilized the results of observation activities and interviews with supervising teachers and school principals to obtain comprehensive data. The research results show that extracurricular activities at SDN Aengdake I are able to have a positive impact on student development, both in physical, emotional and social aspects. The teacher's active role in designing and guiding activities is the main factor in the success of this extracurricular program.